The Shortest Distance Between Gamelan and Electronics: Creating a “nexus of understanding” at Martin Bartlett’s Summer Intensives (Vancouver, 1986–1992) - Bellemare, Laurent (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2020)
During Expo 86, composer Martin Bartlett showcased his commitment to having Javanese music settle in Vancouver. By organizing a month-length workshop on Indonesian performing arts, he secured the Indonesian Embassy’s gift of a full Javanese gamelan to Simon Fraser University. The success of this first workshop encouraged Bartlett to repeat the experience for several years. In the summer of 1988, the event took an unexpected turn by concurrently featuring gamelan and electronic music workshops side by side. Dubbed “Dance and Music of Two Worlds,” it provided a unique place of encounter in which Javanese music traditions coexisted with electronic arts. Although the two hardly intermingled, the 1980s and 1990s saw many interdisciplinary productions mixing gamelan and electronics emerge from participating students. At the time, this relatively unexplored encounter between sound worlds put a stamp on the regional identity of the Vancouver gamelan scene, one still echoing today.